PENGARUH PROFESIONALISME, TEKANAN KETAATAN, PENGALAMAN AUDITOR, DAN PERSEPSI ETIS TERHADAP AUDIT JUDGEMENT (Studi Empiris pada Kantor Akuntan Publik di Padang, Palembang, dan Pekanbaru) - Faras Rizki Ramadhan; Desmiawaty Desmiawaty; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study isto examine theeffect of proffesionalism, pressure of loyalty, experience, and perception influence to audit judgement was taken by auditor. Audit judgement is used in order to produce the final opinions about the fairness of a company’s financial statement to be issued by the auditor.The quality produced by the auditor judgement may be interrupted because of a situationthat occurred in the ethical dilemma that will affect the auditor’s take an ethical decision that will affect the resulting judgement.Accuracy auditor to generate audit judgement influenced by proffesionalism, pressure of loyalty, exprerience and perception influence.The study population was all auditor who worked on the firm in Padang City, Palembang City, and Pekanbaru City, and has worked at least 2 year experience. Sampling was done using a simple sampling to obtain as many as 105 respondents.The data used in this study is primary data in the form of a questionnaire.From 105 questionnaires has distributed, only 92 questionnaires can be processed.The result of this study showed that proffesionalism, pressure of loyalty, experience, and perception influence has a positive influence on audit judgement.Suggestion for futher research that could add situational factors such as organizational culture and and ethical values as well as more variable.Keyword : Proffesionalism, Pressure of Loyalty, Experience, Perception Influence and Audit Judgement.